Learners’ Experiences In Using Online-Based Application During COVID-19 Pandemic In English Department - Nuryansyah Adijaya; Zuriyati Zuriyati; Ninuk Lustyantie; Muhamad Sofian Hadi; Aulia Maharani (Universitas Sulawesi Barat, 2021)
During the COVID-19 pandemic, all activities such as teaching and learning activities at college must be carried out online. This online learning activity utilizes online-based learning applications. Every students certainly have their positive and negative response and opinion about using online learning application. Therefore, this research aims to obtain and describe about learners' experiences in using online-based learning application during COVID-19 pandemic in English Department. The method of this research is qualitative descriptive study. Data collection was conducted by questionnaire and 1 questions for polling. The respondents of this research were 40 English department learners. To gain in-depth explanation, the researchers also interviewed 7 learners through WhatsApp application. The results showed that students gave positive and negative responses to the use of online-based learning applications.